2000
DOI: 10.2527/2000.78123177x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary chromium-L-methionine on glucose metabolism of beef steers.

Abstract: Thirty-six crossbred steers (288 +/- 3.7 kg initial BW) were used to determine the effect of Cr, as chromium-L-methionine, on glucose tolerance and insulin sensitivity in beef calves. Calves were fed a control diet or the diet supplemented with 400 or 800 microg Cr/kg of diet as chromium-L-methionine. Calves were kept in drylots (six calves/pen; two pens/dietary treatment). Steers were caught twice a day in locking headgates and individually fed their respective diets for a period of 22, 23, or 24 d prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
4
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 0 publications
7
54
4
6
Order By: Relevance
“…11 Unlike most earlier reports, the present findings indicated that inorganic trivalent Cr might also be potentially effective in enhancing nutrient utilization in anestrous dairy calves. The effect of dietary supplementation of Cr on nutrient intake in dairy cattle is contradictory and some of the earlier investigations reported no significant effect on the intake parameters.…”
Section: Intake and Apparent Digestibility Of Nutrients And Body Weigcontrasting
confidence: 55%
“…11 Unlike most earlier reports, the present findings indicated that inorganic trivalent Cr might also be potentially effective in enhancing nutrient utilization in anestrous dairy calves. The effect of dietary supplementation of Cr on nutrient intake in dairy cattle is contradictory and some of the earlier investigations reported no significant effect on the intake parameters.…”
Section: Intake and Apparent Digestibility Of Nutrients And Body Weigcontrasting
confidence: 55%
“…Kegley et al (2000) reported that supplemental Cr, as chromium-L-methionine, increased glucose clearance rate after an insulin infusion and increased the insulin response to an intravenous glucose challenge in growing calves with functioning rumens. Vincent (2004) reported that various trivalent chromate compounds have been used as nutritional supplements, weight-loss agents, and muscle-development agents in humans and as feed additives in domestic animals.…”
Section: Resultsmentioning
confidence: 98%
“…Isto foi demonstrado por Yang et al (1996) que suplementaram bovinos leiteiros de diferentes categorias com Cr e observaram aumento significativo de 15% no consumo de matéria seca e tendência de produção de leite superior em primíparas, mas não em vacas multíparas. Outros fatores a serem considerados são os níveis e a biodisponibilidade da forma química do mineral na dieta basal, pois se adequados, podem justificar a ineficiência de sua inclusão Galloway;Fakler, 2000).…”
Section: Resultsunclassified